2004
DOI: 10.1038/nsmb813
|View full text |Cite
|
Sign up to set email alerts
|

The SINE-encoded mouse B2 RNA represses mRNA transcription in response to heat shock

Abstract: Cells respond to changes in environmental conditions via orchestrated modifications in gene expression. For example, in response to heat shock, cells execute a program of gene-specific transcriptional activation and repression. Although the activation of genes upon heat shock has been widely studied, the mechanism of mRNA transcriptional repression upon heat shock is unexplained. Here we show that during the heat shock response in mouse cells, a small noncoding RNA polymerase III transcript, B2 RNA, associates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
215
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(224 citation statements)
references
References 45 publications
3
215
0
1
Order By: Relevance
“…Expression of this RNA is increased up to 100-fold in response to environmental stresses such as heat shock (Liu et al 1995;Allen et al 2004). Coimmunoprecipitation and binding experiments have provided evidence that B2 RNA associates with RNA pol II upon heat shock, and in vivo and in vitro transcription experiments have revealed that B2 RNA inhibits RNA pol II by preventing the formation of active preinitiation complexes Espinoza et al 2004).…”
Section: Mouse B2 Rnamentioning
confidence: 99%
“…Expression of this RNA is increased up to 100-fold in response to environmental stresses such as heat shock (Liu et al 1995;Allen et al 2004). Coimmunoprecipitation and binding experiments have provided evidence that B2 RNA associates with RNA pol II upon heat shock, and in vivo and in vitro transcription experiments have revealed that B2 RNA inhibits RNA pol II by preventing the formation of active preinitiation complexes Espinoza et al 2004).…”
Section: Mouse B2 Rnamentioning
confidence: 99%
“…Our laboratory reported that 2 ncRNAs, mouse B2 RNA and human Alu RNA, repress mRNA transcription by binding to Pol II during the cellular heat shock response (3,4). B2 and Alu RNAs are transcribed by RNA polymerase III from short interspersed elements (SINEs) (5).…”
mentioning
confidence: 99%
“…B2 RNA is synthesized after heat shock and specifically binds polymerase II and inhibits transcription. (11,12) Thus, selective pressure as a factor maintaining, at least, some ''functionless'' repeats in the eukaryotic genome should not be neglected. The functional role of non-conventional classes of non-coding RNAs was reviewed recently by Mattick.…”
Section: Introductionmentioning
confidence: 99%